2011
DOI: 10.1007/s11033-011-0791-5
|View full text |Cite
|
Sign up to set email alerts
|

Study on the association of p53 codon 72 polymorphisms with risk of gastric cancer in high incidence Hexi area of Gansu Province in China

Abstract: To investigate the possible association of P53 codon 72 Arg/Pro polymorphisms with risk of gastric cancer in the high incidence Hexi area of Gansu province in China. Blood samples from 140 patients with gastric carcinoma and 125 healthy controls were collected in Hexi area of Gansu province. Polymorphism of P53Arg72Pro was genotyped by PCR-TaqMan. For detection Helicobacter pylori infection, Warhin-Starry staining was used. Three kinds of polymorphisms of P53Arg72Pro were Arg/Arg, Arg/Pro, Pro/Pro. The frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Zang et al, (2003) reported that Arg/Arg genotype is associated with high risk of gastric cancer. Ke-Xiang et al, (2012) in a Chinese population showed that Arg/Pro+Pro/Pro genotypes increased risk of gastric cancer. No significant association between p53 alleles and gastrointestinal cancers was reported by Mojtahedi et al, (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Zang et al, (2003) reported that Arg/Arg genotype is associated with high risk of gastric cancer. Ke-Xiang et al, (2012) in a Chinese population showed that Arg/Pro+Pro/Pro genotypes increased risk of gastric cancer. No significant association between p53 alleles and gastrointestinal cancers was reported by Mojtahedi et al, (2010).…”
Section: Discussionmentioning
confidence: 99%
“…The study of genetic variation could provide future implications for preventive and early intervention strategies. Many studies have suggested that GC development, treatment, and clinical outcome are associated with variations in several genes, including EGFR [48, 49], glutathione-S-transferase M1 and T1 [50], p53 [51], E-cadherin( CDH1 ) [52], and cyclooxygenase-2 [53]. We showed that lifestyle (such as meal duration) and clinical examination (such as the status of glutamic pyruvic transaminase) were significantly associated with GC ZHENG, and rs13689 in CDH1 is correlated with the GC ZHENG type [54].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, studies in Korea reported that Pro/Pro genotype was associated with increased risk of this neoplasm [95, 126]. While in a Chinese population, Ke-Xiang et al [123] showed that Arg/Pro + Pro/Pro genotypes increased risk of GC. Corroborating these data, a recent meta-analysis suggests that the Pro/Pro genotype was associated with several types of cancer, including GC [93].…”
Section: Tp53 Polymorphisms and Risk Of Esophageal And Gastric Cancermentioning
confidence: 99%
“…The genetic susceptibility to gastric carcinogenesis related to TP53 polymorphisms may be attributed to several factors, including the accumulation and interaction of SNPs [124, 129], gene-environmental interactions [93], age [128, 131], H. pylori infection [123], bile or acid reflux, and smoking [137]. …”
Section: Tp53 Polymorphisms and Risk Of Esophageal And Gastric Cancermentioning
confidence: 99%